Development of brannerite glass‐ceramics for the immobilization of actinide‐rich radioactive wastes. Issue 9 (1st June 2017) - Zhang, Yingjie; Kong, Linggen; Karatchevtseva, Inna; Aughterson, Robert D.; Gregg, Daniel J.; Triani, Gerry
Abstract: Brannerite‐based glass‐ceramics have been developed as potential waste forms for the immobilization of actinide‐rich radioactive wastes. For the first time, the formation of brannerite phases in glass has been demonstrated using uranium (U) and plutonium (Pu) with additions of gadolinium and hafnium as neutron absorbers. Both XRD and SEM‐EDS confirm that brannerite is the dominating phase with compositions close to Y0.5 U0.5 Ti2 O6, Gd0.2 Pu0.3 U0.5 Ti2 O6, and Gd0.1 Hf0.1 Pu0.2 U0.6 Ti2 O6 internally crystallized in the glass. TEM SAED and Raman spectroscopy reveal the typical structure and vibration modes for brannerite. In addition, the presence of U 5+ species as designed in the formulations has been confirmed by diffuse reflectance spectroscopy. More importantly, the U and Pu were partitioned exclusively in the ceramic phases with no detectable actinide in the glass.